2007
DOI: 10.1002/ana.21068
|View full text |Cite
|
Sign up to set email alerts
|

Sustained neocortical neurogenesis after neonatal hypoxic/ischemic injury

Abstract: The young nervous system has long been known to possess a greater capacity to recover from injury than the adult system. Our data indicate that H-I injury in the neonatal brain initiates an enduring regenerative response from the subventricular zone. These data suggest that additional mechanisms than those previously surmised contribute to the remarkable ability of the immature brain to recover from injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
122
3
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 147 publications
(143 citation statements)
references
References 37 publications
10
122
3
8
Order By: Relevance
“…Recent evidence indicates that neurogenesis persists beyond the fetal period and into adulthood in certain areas of the brain including the subventricular zone of the lateral ventricles and the subgranular zone of the dentate gyrus of the hippocampus [Toni et al, 2008]. In neonatal rats with experimental hypoxic-ischemic injury, sustained neurogenesis persists in the subventricular zone for months after injury and continues to populate the cerebral cortex with new neurons [Yang et al, 2007]. A similar phenomenon has been shown to occur in adult rodents after stroke [Lichtenwalner and Parent, 2006].…”
Section: Mechanisms For Plasticity In the Central Nervous Systemmentioning
confidence: 84%
“…Recent evidence indicates that neurogenesis persists beyond the fetal period and into adulthood in certain areas of the brain including the subventricular zone of the lateral ventricles and the subgranular zone of the dentate gyrus of the hippocampus [Toni et al, 2008]. In neonatal rats with experimental hypoxic-ischemic injury, sustained neurogenesis persists in the subventricular zone for months after injury and continues to populate the cerebral cortex with new neurons [Yang et al, 2007]. A similar phenomenon has been shown to occur in adult rodents after stroke [Lichtenwalner and Parent, 2006].…”
Section: Mechanisms For Plasticity In the Central Nervous Systemmentioning
confidence: 84%
“…Accumulating evidence suggests that HI injury promotes extensive cell proliferation in the SVZ of the rodent brain. 14,[77][78][79][80][81][82][83] Several studies in which P6 and P7 rats and P10 mice were subjected to moderate HI showed that the SVZ expands in size, illustrated by increased cresyl-violet staining and nestin-positive cells in the ipsilateral SVZ. 78,79,83 Furthermore, an increase in BrdU þ cells was observed in the affected SVZ from 1 week to 3 weeks after HI, implying that cell proliferation is stimulated in this region.…”
Section: Neurogenesis After a Hypoxic-ischemic Insultmentioning
confidence: 99%
“…Several studies observed a significant increase in Dcx/BrdU double-positive cells in the SVZ, striatum, and cortex from 1 to 4 weeks after injury. 77,79,[81][82][83] These double-positive cells were clustered in chains in the striatum and cortex and displayed the morphology of migrating neuroblasts. [82][83][84] Studies investigating the differentiation rate of proliferating cells into neurons and their survival show contradicting results.…”
Section: Cell-fate Commitment Of Proliferating Cells In the Subgranulmentioning
confidence: 99%
See 2 more Smart Citations